Piloting and validating an innovation to triage patients presenting with cough to community pharmacies in Western Australia - Jiwa, Moyez; Hughes, Jeff; Sriram, Deepa; Birring, S.; Meng, Xingqiong (Rosie); Cecchele, G.; Cooke, J.; Ng, N. (Radcliffe Medical Press Ltd., 2012)
Aim: To develop a tool to assist community pharmacists to triage patients presenting with cough and to validate this against an established cough-specific quality of life (QoL) measure. Methods: A decision-support tool, the Pharmacy Cough Assessment Tool (PCAT) was developed with reference to published guidelines and a team of clinical experts. The PCAT was validated against the Leicester Cough Questionnaire (LCQ). It was then administered at four community pharmacies in Perth, Western Australia to assess the scope to recruit and follow up participants, and to estimate the proportion of participants who would be advised to consult a general practitioner (GP). The reported outcomes of the consultations with doctors were also recorded. Results: Ninety-nine subjects were recruited over 12 weeks. Thirty-seven participants were advised to consult a GP for further assessment with reference to the PCAT; seven attended their doctor. The LCQ scores of those referred to their GP were significantly lower, indicating a poorer quality of life (adjusted mean and range 13.16 [11.87, 14.46]; non-referred 15.82 [14.47, 17.18]; P < 0.001). Scores of this magnitude have previously been shown to identify patients with chronic respiratory conditions. A smaller group of participants also had a poor quality of life based on LCQ scores but were not referred to their GP. Of the seven participants who made an appointment with their GP, most were prescribed treatment or referred for investigation. There was no significant difference in LCQ score based on gender, or decision to consult a GP. Conclusions: The PCAT identifies patients with cough who might benefit from medical advice and may feasibly be used as an initial screening tool in the community pharmacy setting.